2013
DOI: 10.1177/0950017012469064
|View full text |Cite
|
Sign up to set email alerts
|

‘Stressed out of my box’: employee experience of lean working and occupational ill-health in clerical work in the UK public sector

Abstract: Occupational health and safety (OHS) is under-researched in the sociology of work and employment. This deficit is most pronounced for white-collar occupations. Despite growing awareness of the significance of psychosocial conditions -notably stress -and musculoskeletal disorders, white-collar work is considered by conventional OHS discourse to be 'safe'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
96
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 31 publications
5
96
1
2
Order By: Relevance
“…Drawing on qualitative data, the authors examine how teams emerged from different sites within HMRC, and with different effects within different teams and workers. While the authors partially corroborate other reports (Carter et al, 2011(Carter et al, , 2013 of workers dissatisfaction with the deskilling, task simplification and standardisation that resulted from the introduction of Lean, they also seek to understand the alternative responses by some employees who reported some appreciation of Lean, especially the use of teamwork. While national-level site teams engaged in problem-solving that included the authority to make changes to standard operating protocols, at most HMRC sites teamwork was reinvented as workplace co-operation and information-sharing among employees with a primary aim of achieving operational targets.…”
Section: The Special Issuesupporting
confidence: 70%
See 1 more Smart Citation
“…Drawing on qualitative data, the authors examine how teams emerged from different sites within HMRC, and with different effects within different teams and workers. While the authors partially corroborate other reports (Carter et al, 2011(Carter et al, , 2013 of workers dissatisfaction with the deskilling, task simplification and standardisation that resulted from the introduction of Lean, they also seek to understand the alternative responses by some employees who reported some appreciation of Lean, especially the use of teamwork. While national-level site teams engaged in problem-solving that included the authority to make changes to standard operating protocols, at most HMRC sites teamwork was reinvented as workplace co-operation and information-sharing among employees with a primary aim of achieving operational targets.…”
Section: The Special Issuesupporting
confidence: 70%
“…For example, Turner (2012) argues that the introduction of Lean benefits employees due to improved skills development and greater increased involvement in process improvement decisions. Other scholars claim a negative impact on at least some managers and employees as a result of work intensification and disempowerment (AndersonConnelly, Grunberg, Greenberg, & Moore, 2002;Carter et al, 2013;Grugulis & Lloyd, 2010;Jones, Latham, & Betta, 2013;Stewart et al, 2009;Torella, Falzon, & Morais, 2012;Vidal, 2007).…”
Section: *Corresponding Author Email: Gregbamber@gmailcommentioning
confidence: 99%
“…As part of the attempt to draw the wider implications of these findings, we set them against what Carter et al had found in their study of Lean in the same organization (Carter et al, 2011a(Carter et al, , 2011b(Carter et al, , 2013a(Carter et al, , 2013b. Our argument here was that Carter et al had taken little or no account of the way in which teamworking operated in HMRC, and that, had they done so, then it might have been easier to understand the differences between their findings and ours-and also between their findings and the results of an official employee survey undertaken at around the same time (Civil Service People Survey, 2011).…”
mentioning
confidence: 84%
“…Carter et al (2015: 4) place their own work squarely in this tradition, but we cite four of their papers (Carter et al, 2011a;2011b;2013a;2013b) and address in a direct way the issues they raise-this is precisely what has generated their response. They might not like how we interpret their work, and they are, of course, quite entitled to respond to this interpretation.…”
mentioning
confidence: 99%
See 1 more Smart Citation